Minat Remaja Dalam Mengikuti Shalat Berjamaah - Chaira Saidah Yusrie; Indra Noviansyah; Muhamad Nasrudin (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2021)
The aims of the research are to: 1) obtain data on the interest of adolescents in participating in jamaah prayers at the mosque; 2) obtain data on the factors that cause the low interest of adolescents to attend jamaah prayer at the mosque 3) find out how to overcome the causes of the lack of interest of adolescents in participating prayer at the mosque. The research was conducted in Cipayung Village, Kec. Cibinong, Bogor Regency. Research data were collected using questionnaires and documentation techniques. The research instrument used a questionnaire to obtain data on interest in praying in congregation and documentation was used to obtain other data needed in writing reports, and research data were analyzed descriptively with percentages. The results of the study recommend: 1) Teenagers should always motivate themselves to do positive things and not be carried away by negative associations. 2) For scholars to be more active in conducting coaching to teenagers. 3) For further researchers, it is recommended to examine the interest of teenagers in participating in praying at the mosques for Madrasah Aliyah level. Chaira Saidah Yusrie IAI Nasional Laa Roiba Bogor Indra Noviansyah IAI Nasional Laa Roiba Bogor Muhamad Nasrudin IAI Nasional Laa Roiba Bogor